Plasticizing effect on polyethylene oxide doped ammonium perchlorate - Pratap, Rana; K Singh, Pramod; Sharma, Tejas; Singh, Vijay; Alheety, Mustafa A; Kumar, Sushant; Madkhli, Aysh Y; Noor, Im; Zakariya’u, Ibrahim; Singh, Abhimanyu (SAGE Publications, 2022)
Plasticized polymer complex films of polyethylene oxide with ammonium perchlorate (NH4ClO4) are synthesized by using solution cast technique. Propylene carbonate (PC) used as dopant to enhance conductivity of polymer electrolyte. The prepared films are characterized in detail using X-ray diffraction, infrared spectral analysis, transient ionic current, and electrochemical impedance studies. Plasticized polymer electrolyte shows high ionic conductivity (∼10−4 S/cm) which appear as novel electrolyte for electrochemical devices.